JURIDICAL APPROACH TO THE OPERATIONAL TECHNICAL EVIDENCE IN ACCORDANCE WITH ARTICLE 146 OF LAW NUMBER 1 OF 2009 ON AVIATION - I Wayan Partama Putra (International Conference on Multidisciplinary Research Perspective, 2025)
Article 146 of the Aviation Law requires carriers to be responsible for losses caused by delays in the transportation of passengers, baggage, and cargo, unless they are able to prove that such constraints were due to weather factors or operational technical issues. However, this legal provision contains significant ambiguities in the phrases "to prove" and "operational technical," which create legal uncertainty. This study examines the impact of this ambiguity on the contractual liability of airlines and the legal protection of passengers. The research analyzes two main issues: the nature of the norm’s ambiguity and its effects on the rights and obligations of the parties involved. The normative juridical method with a conceptual approach and legislation study was employed, alongside grammatical and systematic interpretation analysis of the Aviation Law, the Civil Code, and related regulations. The study finds that the ambiguity in the norm creates legal gaps that can be exploited by airlines, thereby necessitating regulatory revisions to clarify the evidentiary mechanisms and strengthen consumer protection in order to balance rights and obligations in the aviation industry.